2022
DOI: 10.1186/s12959-022-00390-2
|View full text |Cite|
|
Sign up to set email alerts
|

Prognostic value of plasma high mobility group box 1 protein and histone H3 levels in patients with disseminated intravascular coagulation: a multicenter prospective cohort study

Abstract: Background We compared the prognostic value of serum high mobility group box 1 protein (HMGB1) and histone H3 levels with the International Society on Thrombosis and Haemostasis (ISTH) disseminated intravascular coagulation (DIC) scores for 28-day in-hospital mortality in patients with DIC caused by various underlying diseases. Methods We conducted a multicenter prospective cohort study including two hematology departments, four emergency departmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 61 publications
(44 reference statements)
0
5
0
Order By: Relevance
“…To evaluate which biological processes of histones and Mg 2+ are involved in the pathogenesis of sepsis, bioinformatic analysis was performed (21). Putative targets associated with MgSO 4 and histones (main pathogenic types: H3 and H4 (5,22)) were harvested from the DrugBank, STITCH, or SuperPred databases. The targets in sepsis were used from web-based GeneCard and DisGeNET databases.…”
Section: Bioinformatics Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…To evaluate which biological processes of histones and Mg 2+ are involved in the pathogenesis of sepsis, bioinformatic analysis was performed (21). Putative targets associated with MgSO 4 and histones (main pathogenic types: H3 and H4 (5,22)) were harvested from the DrugBank, STITCH, or SuperPred databases. The targets in sepsis were used from web-based GeneCard and DisGeNET databases.…”
Section: Bioinformatics Analysismentioning
confidence: 99%
“…To evaluate which biological processes of histone and Mg 2+ are involved in the pathogenesis of sepsis. We determined the correlative targets of MgSO 4 , histones (main pathogenic types: H3 and H4 (5,22)), and sepsis through bioinformatics methods. Further Gene Ontology analysis showed that MgSO 4 may play an important part in histone-induced septic injury through coagulation-related biological process regulation (Fig.…”
Section: Circulating Histone Levels In Relation To Coagulation Parame...mentioning
confidence: 99%
“…Author details 1 Department of Hematology, Fukushima Medical University, 1 Hikarigaoka, Fukushima 960-1295, Japan. 2 Scientific Research Works Peer Support Group (SRWS-PSG), Osaka, Japan.…”
Section: Open Accessmentioning
confidence: 99%
“…Following publication of the original article [ 1 ], it was reported that the term ‘plasma’ should have been used in place of ‘serum’ in the title, abstract, methods, results, discussion, conclusions, and supplementaly information, and prior researches in reference number 11, 12, 13, and 15. It was also reported that the term ‘plasma or serum’ should have been used in place of ‘serum’ in a prior research in reference number nine.…”
mentioning
confidence: 99%
See 1 more Smart Citation